Development and Validation of UV-spectrophotometric Method for Estimation of Gallic Acid in Acalypha indica Leaf Extract and its Cellulose Nanoparticle Formulation - Sneha, Kumar; Geetha, Muniyappa; Swapna, Birendra; Setty, Ramachandra Setty Siddam (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim/Background: Quantification of Gallic acid in the hydro-alcoholic extract of Acalypha indica and extract loaded cellulose nanoparticles is a characteristic parameter to assess the entrapment efficiency of nanoparticles. Gallic acid is one of the major phenolic acids identified in leaf extract of Acalypha indica; hence, it was chosen to be estimated. Materials and Methods: A UV spectrophotometric method was developed using distilled water as a suitable solvent system to estimate Gallic acid. The method was validated for parameters such as linearity, precision, robustness and accuracy according to the ICH guidelines. The λmax of 256nm was observed for both Gallic acid and Acalypha indica extract, which indicated specificity of the method for further analysis. Results: Linearity was established between the concentration range of 5-30 μg/ml with a regression coefficient of 0.999 signifying good correlation between the concentration and absorbance. Average percent recovery of 97.6% demonstrated the accuracy of the method. The recorded RSD of <2% in precision validation indicated the correctness of the method. Ruggedness and robustness of the method were established with RSD of <2% suggesting that the analysis is unaffected with change in analyst and wavelength. The detectable and quantifiable limits of Gallic acid were found be 0.045 μg/ml and 0.119 μg/ml respectively, which demonstrated the sensitivity of the method as well. Conclusion: From the above results, it was concluded that the UV-spectrophotometric method can be employed to estimate Gallic acid in both leaf extract and extract loaded pharmaceutical formulations.
Keywords: Gallic acid; UV spectrophotometer; Acalypha indica; Cellulose nanoparticles; Method validation; Leaf extract